From Classroom to Creativity: SMART-PUBLISH Toolkit for Special Needs Entrepreneurship in Publishing Children’s Picture Books - Arumugam, Shyielathy; Mustafa, Mazlina Che; Abdullah, Norazilawati binti; Shamsudin, Iylia Dayana Binti; Jamil, Mohd Ridhuan bin Mohd; Dzainudin, Masayu binti (Journal of Ecohumanism, 2024)
Entrepreneurship education equips individuals with the skills necessary to establish and manage businesses. However, in Malaysia, disability employment is often regarded as an act of charity, which perpetuates stigma. This study addresses this issue by developing the SMART-PUBLISH Kickstarter Toolkit designed to facilitate the authoring, illustrating, and publishing of children’s picture books by students with special needs. The research was conducted in three phases following the Richey & Klein (2007) model: (I) Needs Analysis, (II) Design and Development, and (III) Usability Testing. Phase I involved an online survey with 170 special education educators in Kuala Kangsar, revealing strong support for entrepreneurship education (M=3.69, SD=0.96), the promotion of entrepreneurial skills (M=3.89, SD=0.83), and the need for a toolkit (M=3.99, SD=0.78). During Phase II, 12 experts validated the toolkit constructs and items using the Fuzzy Delphi Method (FDM), achieving consensus across all criteria. In Phase III, the usability of the toolkit was evaluated with 27 special education educators, who provided over 70% positive consensus on all usability constructs.The study concludes that the SMART-PUBLISH Kickstarter Toolkit empowers special education teachers to implement innovative teaching methods, thereby fostering entrepreneurship and creativity among students with special needs.